Financial intelligence : a manager's guide to knowing what the numbers really mean - Berman, Karen, 1962-; Knight, Joe, 1963-; Case, John, 1944- (Boston, Mass. : Harvard Business Review Press, 2013)
""Inc." magazine calls it one of "the best, clearest guides to the numbers" on the market. Readers agree, saying it's exactly "what I need to know" and calling it a "must-read" for decision makers without expertise in finance. Since its release in 2006, "Financial Intelligence" has become a favorite among managers who need a guided tour through the numbers--helping them to understand not only what the numbers really mean, but also why they matter. This new, completely updated edition brings the numbers up to date and continues to teach the basics of finance to managers who need to use financial data to drive their business. It also addresses issues that have become even more important in recent years--including questions around the financial crisis and those around broader financial and accounting literacy. Accessible, jargon-free, and filled with entertaining stories of real companies, Financial Intelligence gives nonfinancial managers the confidence to understand the nuance beyond the numbers--to help bring everyday work to a new level."--Publisher's website.
Part one: The art of finance (and why it matters). You can't always trust the numbers -- Spotting the assumptions, estimates, and biases -- Why increase your financial intelligence? -- The rules accountants follow- and why you don't always have to -- Part one toolbox: getting what you want; the players and what they do; reporting obligations of public companies -- Part two: The (many) peculiarities of the income statement. Profit is an estimate -- Cracking the code of the income statement -- Revenue: the issue is recognition -- Costs and expenses: no hard-and-fast rules -- The many forms of profit -- Part two toolbox: Understanding variance; profit at non-profits; a quick review: "percent of" and "percent change" -- Part three: The balance sheet. Understanding balance sheets basics -- Assets: more estimates and assumptions (except for cash) -- On the other side: liabilities and equity -- Why the balance sheet balances -- The income statement affects the balance sheet -- Part three toolbox: Expense? or capital expenditure?; the impact of mark-to-mark accounting -- Part four: Cash is king. Cash is a reality check -- Profit [does not equal] cash (and you need both) -- The language of cash flow -- How cash connects with everything else -- Why cash matters -- Part four toolbox: Free cash flow; even the big guys can run out of cash -- Part five: Ratios: learning what the numbers are really telling you. The power of ratios -- Profitability ratios: the higer the better (mostly) -- Leverage ratios: the balancing act -- Liquidity ratios: can we pay our bills? -- Efficiency ratios: making the most of your assets -- The investor's perspective: the "big five" numbers and shareholder value -- Part five toolbox: Which ratios are most important to your business?; the power of percent of sales; ratio relationships; different companies, different calculations -- Part six: How to calculate (and really understand) return on investment. The building blocks of ROI -- Figuring the ROI
Includes index.
Includes bibliographical references and index.
Print version record.
Keywords: Financial statements; Cash management; Corporations -- Finance; Information financière -- Guides, manuels, etc; États financiers -- Guides, manuels, etc; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Cash management; Corporations -- Finance; Financial statements; elektronické knihy; electronic books